Improved performance dynamic voltage restorer with seven level multilevel inverter - Chandrasekaran K.; Ramachandaramurthy V.K. (Research India Publications, 2023)
In this paper, a seven level cascaded multilevel inverterbased Dynamic Voltage Restorer (DVR) using multicarrier SPWM technique controller is proposed to handle deep voltage sags, swells and voltage harmonic disturbances on a threephase system.New innovative simple controller schemes based d-q theory to overcome the disadvantages of the existing controller schemes by reducing the complexity, number of signal measurements and computing time has been developed for this model. The control scheme provides ability to control the zero sequence voltage during unbalance fault period, capable to track the phase angle of the supply voltages continually and adaptivelyand low switching frequencies of the phase shift PWM which decrease the switching loss and increase the efficiency.The improved DVR is verified through extensive simulation using PSCAD/EMTDC. The DVR gives good control dynamics with minimum transient current overshoot. Good results under transient performance obtained. Research India Publications.